P.N345K mutation in TARDBP in a patient with familial amyotrophic lateral sclerosis: An autopsy case. Issue 4 (24th May 2019) - Takeda, Takahiro; Iijima, Mutsumi; Shimizu, Yuko; Yoshizawa, Hiroshi; Miyashiro, Mayu; Onizuka, Hiromi; Yamamoto, Tomoko; Nishiyama, Ayumi; Suzuki, Naoki; Aoki, Masashi; Shibata, Noriyuki; Kitagawa, Kazuo
Abstract : We report the neuropathology of a patient with a family history of amyotrophic lateral sclerosis (ALS) and a p.N345K mutation in the transactivation response DNA‐binding protein 43 kDa (TDP‐43) gene ( TARDBP ). A 62‐year‐old man had bulbar palsy with progressive weakness in the extremities. Neurological examination revealed evident upper motor neuron signs and lower motor neuron involvement corroborated by needle electromyography. The patient was diagnosed as having probable ALS according to the revised El Escorial diagnostic criteria and was eventually diagnosed with familial ALS. At 65 years of age, respiratory failure became critical, and artificial ventilation was initiated. At 70 years of age, the patient died from a urinary tract infection. Histopathological investigation showed Bunina bodies in the remaining motor neurons and anterolateral funicular myelin pallor in the spinal cord. TDP‐43‐positive cytoplasmic inclusions were quite rare in the spinal cord motor neurons, being predominantly present in the glial cells (especially astrocytes) of the spinal cord anterior horn. Although the reason for the preferential vulnerability of spinal glial cells to TARDBP mutations remains unclear, our findings indicate that TARDBP p.N345K mutation could have an influence on the topography of TDP‐43 aggregation.